Efforts to Improve Pedestrian Facility Services in the Jati Mulya – Bekasi Lrt Station Area - Rizky Setyaningsih; Panji Pasa Pratama (Publikasi Indonesia, 2025)
The Jatimulya Bekasi LRT station has an important role as a public transportation hub, and the surrounding pedestrian facilities need to be assessed to meet the needs of users. Dissatisfaction with pedestrian facilities can hinder the success of the public transportation system. This study aims to assess satisfaction with pedestrian facilities at the station. The method used is Importance Performance Analysis (IPA), which groups service attributes based on importance and performance. Assessments were carried out on 24 facility attributes in accordance with the Minimum Service Standards, including pedestrian paths, crossing facilities, surveillance cameras, security officers, waiting areas, and facilities for the disabled. The results of the analysis showed that 84.4% of service attributes had met expectations, while 15.6% still needed improvement. The four attributes that need immediate improvement are crossing facilities, CCTV security systems, waiting areas for advanced transport, and pedestrian path design. Recommendations for improvement include improving crossing facilities, installing CCTV and adequate lighting, providing comfortable waiting areas with shade facilities, and designing pedestrian lanes that separate vehicles and pedestrians to ensure smooth traffic and safety.